S100, alpha-smooth muscle actin and cytokeratin 19 immunohistochemistry in odontogenic and soft tissue myxomas. Issue 8 (August 1995) - Lombardi, T; Lock, C; Samson, J; Odell, E W
Abstract : AIMS–To compare the expression of S100 protein, alpha-smooth muscle actin (alpha-SMA) and keratin 19 in odontogenic myxomas and non-odontogenic myxoid lesions. METHODS–Formalin fixed, paraffin wax embedded tissue from seven odontogenic myxomas, three soft tissue myxomas, six hyperplastic myxoid dental follicles, two intramuscular myxomas, 12 cardiac myxomas, and seven normal dental follicles were examined immunocytochemically for S100 protein, alpha-SMA and cytokeratin 19 using the Streptavidin-biotin method. RESULTS–A minority of odontogenic myxomas (three of seven) were positive for S100 and the staining was of moderate intensity and in all myxofibroblasts. Soft tissue myxomas, normal dental follicles, intramuscular myxomas, and most enlarged myxoid follicles were negative. In the cardiac myxomas the cells forming cords and islands were positive in approximately half (seven of 12), but the dispersed stellate myxoblasts were positive in only two cases. A population of cells in all the odontogenic myxomas and hyperplastic dental follicles contained alpha-SMA, but such cells were sparse in cardiac myxomas and present in only four cases. Cytokeratin 19 was present in odontogenic epithelium of odontogenic myxoma and follicles. CONCLUSIONS–A minority of odontogenic myxomas, but not other oral myxoid lesions, may express S100 protein and this could cause difficulty distinguishing myxoma from myxoid nerve sheath tumours. Sparse myofibroblastic cells occurred in all types of myxoma tested. The epithelium sometimes found within jaw myxomas expresses cytokeratin 19 and this is consistent with an odontogenic origin.